2011
DOI: 10.1007/s10964-011-9707-x
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Mexican American Adolescents’ Academic Success: Considering Family and Individual Factors

Abstract: Mexican American youth are at greater risk of school failure than their peers. To identify factors that may contribute to academic success in this population, this study examined the prospective relationships from 5th grade to 7th grade of family (i.e., human capital [a parent with at least a high school education], residential stability, academically and occupationally positive family role models, and family structure) and individual characteristics (i.e., externalizing symptoms, bilingualism, gender, and imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 52 publications
0
17
0
3
Order By: Relevance
“…The example uses data from Proyeto: La Familia (The Family Project, Roosa, Liu, Torres, Gonzales, Knight, & Saenz, 2008), a longitudinal study of Mexican American families. We tested whether there is a possible interaction of child’s reported academic self-efficacy and positive family role models on the child’s academic performance (e.g., Roosa, O’Donnell, Cham, Gonzales, Zeiders, Tein, Knight, & Umaña-Taylor, 2012). Our analyses are based on 669 families with complete data.…”
Section: Illustrative Examplementioning
confidence: 99%
“…The example uses data from Proyeto: La Familia (The Family Project, Roosa, Liu, Torres, Gonzales, Knight, & Saenz, 2008), a longitudinal study of Mexican American families. We tested whether there is a possible interaction of child’s reported academic self-efficacy and positive family role models on the child’s academic performance (e.g., Roosa, O’Donnell, Cham, Gonzales, Zeiders, Tein, Knight, & Umaña-Taylor, 2012). Our analyses are based on 669 families with complete data.…”
Section: Illustrative Examplementioning
confidence: 99%
“…Schwartz et al (2005) discussed the process that adolescents must go through to arrive at full adult independence. Previous studies with Native American and Latino youth showed that adolescents spend more time engaged in productive behavior and less time engaged in maladaptive behavior when parents were good role models and when parent and adolescent engaged in ongoing communication (Roosa et al, 2012;Sarche & Spicer, 2008), with one study pointing to self-efficacy as a mediator (Pu et al, 2013). For some groups of minority adolescents, developing a positive identity and a strong sense of agency can be quite challenging, because members of some ethnic/racial groups are less likely to have access to key resources, more frequently face discrimination, and are more likely to live in neighborhoods where they are exposed to risks (Burt et al, 2012;Cabrera, 2013).…”
Section: Self-efficacy For Independent Learningmentioning
confidence: 95%
“…Perhaps modeling and guidance functions as a protective factor in communities where life is often pervaded by uncertainty yet there are strong cultural values related to social behavior (e.g., familism in the case of Latinos; child stewardship in the case of Native Americans). Previous studies with Native American and Latino youth showed that adolescents spend more time engaged in productive behavior and less time engaged in maladaptive behavior when parents were good role models and when parent and adolescent engaged in ongoing communication (Roosa et al, 2012;Sarche & Spicer, 2008), with one study pointing to self-efficacy as a mediator (Pu et al, 2013). The reason that modeling did not appear to be as strong a factor for African American adolescents is not fully determinable from the data available.…”
Section: Linear Regressionmentioning
confidence: 97%
“…Stress in the family system impacts child mental health and well-being and is expressed as internalizing and externalizing depressive symptoms. Internalizing symptoms include lack of interest in school, social withdrawal, poor academic achievement, and suicidal ideation while external symptoms include irritability, aggression, and disruptive behaviors (Jaycox et al, 2009; Roosa et al, 2011). Recently, the Center for Disease Control and Prevention (CDC, 2012) reported high rates of depressive symptoms for Hispanic youth (40%) as compared to 26% of all youth.…”
Section: Adaptation and Feasibility Of A Communication Intervention Fmentioning
confidence: 99%